146k views
2 votes
Write the expression in factored form. m^2-4

User Appeiron
by
5.5k points

2 Answers

4 votes

Answer:

(m-2)(m+2)

Explanation:

a²-b²=(a-b)(a+b)

let m be a and 2 be b

m^2-2²=(m-2)(m+2)

User Dinamarie
by
6.1k points
3 votes

For this case we must factor the following expression:


m ^ 2-4

According to the formula of difference of squares we have:


a ^ 2-b ^ 2 = (a + b) (a-b)

We have to:


a = m\\b = 2

So, we have:


m ^ 2-4 = (m + 2) (m-2)

Answer:

The factored expression is:
m ^ 2-4 = (m + 2) (m-2)

User Ibrahim Timimi
by
5.1k points